PARAMETERS CONTROLLING THE GEOMETRY OF DETACHMENT AND FAULT‐BEND FOLDS: INSIGHTS FROM 3D FINITE‐ELEMENT MODELS APPLIED TO THE AHWAZ ANTICLINE IN THE DEZFUL EMBAYMENT, SW IRAN - Khalifeh‐Soltani, Anis; Ghassemi, Mohammad R.; Alavi, Seyed Ahmad; Ganjiani, Mehdi (Journal of petroleum geology, 2023)
Fault‐related folds are present in most tectonic settings and can serve as structural traps for hydrocarbons. These structures have therefore been widely studied by both structural and petroleum geologists using a range of techniques. Approaches include field‐ and seismic‐based methods, and numerical and analogue modelling. Geomechanical models attempt to examine the mechanical and geometric features of folds. This study investigates the effects of variations in a range of parameters, including detachment and ramp geometry, friction coefficient and internal friction angle, on the geometry and development of detachment folds and fault‐bend folds. For this purpose, we ran seven series of numerical, 3D elastic‐plastic finite element models using ABAQUS software (26 model runs in all). Each model set‐up consisted of five layers whose mechanical properties were based on those of stratigraphic units in the Zagros fold‐and‐thrust belt, SW Iran. The models were labelled series A to F and series H. Models in series A investigated the impact of concave, convex, wavy and oblique detachment surfaces on the development of detachment folds; those in series D examined the role of ramp dip and of listric, oblique and wavy ramps on the development of fault‐bend folds. Models in series B and E, and series C and F, examined the effects of variations in the friction coefficient and of the internal friction angle, respectively, on the development of these two classes of folds. Finally, hybrid models in series H were provided to evaluate the results. Major results were as follows. Firstly, the geometry of modelled detachment and fault‐bend folds was found to be influenced by the geometry of the associated ramps and detachment faults. Thus the crests of anticlines and the trough lines of synclines were located at points of maximum curvature and at inflexion points on a wavy detachment fault or wavy ramp, respectively. Second, two important additional factors controlling fold style were identified: the friction coefficient, and the presence of along‐strike geometric variations in the ramp or the detachment fault. Layers with low friction coefficients and high internal friction angles formed detachment folds with thick hinges and thin limbs; conversely, layers with high friction coefficients and low internal friction angles created detachment folds with thick limbs and thin hinges. Application of the results to modelling of the Ahwaz anticline in the Dezful Embayment, SW Iran, was successful, and in general the modelled structure was consistent with that observed in the field.